2021
DOI: 10.1016/j.ijpara.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of population structuring following population genetic analyses of Fasciola hepatica from Argentina

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
5
0
2
Order By: Relevance
“…Beesley et al . ( 2 ) found a high level of population genetic diversity in Argentinean F. hepatica isolates and identified a total of 263 unique genotypes. Ichikawa-Seki et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beesley et al . ( 2 ) found a high level of population genetic diversity in Argentinean F. hepatica isolates and identified a total of 263 unique genotypes. Ichikawa-Seki et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bozorgomid et al (8) analysed the genetic diversity of the nad1 gene from F. hepatica isolates from cattle, sheep and goats in Iran, and found a total of 37 haplotypes, with a high level of population genetic diversity. Beesley et al (2) found a high level of population genetic diversity in Argentinean F. hepatica isolates and identified a total of 263 unique genotypes. Ichikawa-Seki et al (16) revealed that 11 haplotypes belonged to a F. hepatica population and 18 haplotypes belonged to a F. gigantica population in 211 lamellipodia from partial geographical regions of China, and Beja-Pereira et al (5) observed that the 'hybrid Fasciola fluke' type harboured the highest number of haplotypes and presented high haplotype diversity and nucleotide diversity values.…”
Section: Discussionmentioning
confidence: 99%
“…Our ideas are informed from theory and empirical work mostly available for free-living systems: geographic variation in mating systems has yet to be directly addressed in metazoan parasites, despite the fact that many are capable of outcrossing, selfing, and parthenogenesis (e.g., gyrodactylids). However, potential support for geographical variation in parasite mating systems can be indirectly inferred from phylogeographical studies when populations vary in F IS (for example, see, Beesley et al 2021 andLymbery et al 1997).…”
Section: Population-level Differences In Host Social Behavior May Drive Population-level Differences In Parasite Evolutionmentioning
confidence: 99%
“…Clonemates may be more likely to accumulate in species that do not utilize aquatic, three‐host life cycles. Semiterrestrial species that use two animal hosts to complete their life cycles, such as Schistosoma mansoni , including those utilizing metacercaria, such as Fasciola hepatica and Fascioloides magna , potentially accumulate clonemates in definitive hosts (Beesley et al, 2021; Mulvey et al, 1991; Prugnolle et al, 2002; Prugnolle, Choisy, et al, 2004; Theron et al, 2004). This is probably facilitated by the clumped transmission of clonemates after leaving snails and aggregating in small pools ( Sc.…”
Section: Introductionmentioning
confidence: 99%